Rounded Edges: Modernism and Architectural Dialogue in Ho Chi Minh City - H. Hazel Hahn (ABE Journal)
It is widely considered that there is no critical mass of architecture in a homogeneous style in Ho Chi Minh City, in contrast to Hanoi. This essay seeks to establish Ho Chi Minh City’s architectural heritage as a significant one, by arguing that the city does actually possess a critical mass of cohesive, remarkably well-designed buildings in modernist styles. Highlighted here is a unique feature of these modernist buildings: rounded, curved corners as a recurring motif in a dense urban center. The author argues that such buildings, dating from the 1920s through the 1970s, have provided the center of Ho Chi Minh City unique, cohesive, and striking characteristics and that they form one of the great ensembles of modernist architecture anywhere. This essay aims to re-locate the place of Ho Chi Minh City on the world map of the circulation of modernism, by emphasizing the internal dynamic of the city’s architectural evolution that transcends the colonial-postcolonial divide, and highlighting the evolution of forms revealing a continuity in spite of event-based ruptures in history. The significant presence of modernist buildings with curved corners in Phnom Penh, and their similarities to those of Ho Chi Minh City, suggest that regional circulation also played a crucial role.